The alleged tension between the Global Compact for Safe, Orderly and Regular Migration and state sovereignty: 'Much Ado about Nothing'?. (27th May 2020) - Capone, Francesca
Abstract: In a landmark effort to finally acknowledge the necessity to jointly respond to the global phenomenon of large movements of refugees and migrants, the process initiated in 2016 with the approval of the New York Declaration for Refugees and Migrants eventually led to the adoption of two UN Global Compacts, respectively the Global Compact for Safe, Orderly and Regular Migration (GCM) and the Global Compact on Refugees (GCR). Despite the enthusiastic support shown at first by the international community, the GCM negotiations have been more controversial and ultimately shaken by the clamorous withdrawals of several states. The main argument used by the withdrawing governments to justify the sudden refusal to adopt the GCM was based on the claim that the document − although non-binding − undermines the 'sovereign right' of the state. Such a claim, given the centrality that the principle of state sovereignty has acquired since the Peace of Westphalia, deserves to be further analysed from an international law perspective by resorting to the 'sovereignty test' developed by Schrijver. The present work, after briefly introducing the main tenets of the GCM, applies the 'sovereignty test' to the GCM to dissect the alleged tension between state sovereignty on the one hand and the shared approach to international migration envisaged by the pact on the other. This article's ultimate goal is to prove that the GCM does not aim to restrain state sovereignty; rather, it strives to remind states of existing international commitments already undertaken at the regional and global level.